Singing the Women Back Up: Art for Social Change and the Empowerment of Women - Kasat, Pilar Amparo (Curtin University, 2020)
This thesis examines art for social change as a decolonising methodology. Four case studies set in colonial-settler societies discuss how women of colour and Indigenous women use art for social change not only to tell their own stories and reclaim their individual power but also to exert power in their collective fight for social justice. The thesis suggest that their creative practices are building a language of resistance that is resonating across the world.